Analyzing the extent and influence of occupational licensing on the labor market - Morris M. Kleiner; Alan B. Krueger (Institute for the Study of Labor (IZA), 2011)
This study examines the extent and influence of occupational licensing in the U.S. using a specially designed national labor force survey. Specifically, we provide new ways of measuring occupational licensing and consider what types of regulatory requirements and what level of government oversight contribute to wage gains and variability. Estimates from the survey indicated that 35 percent of employees were either licensed or certified by the government, and that 29 percent were fully licensed. Another 3 percent stated that all who worked in their job would eventually be required to be certified or licensed, bringing the total that are or eventually must be licensed or certified by government to 38 percent. We find that licensing is associated with about 18 percent higher wages, but the effect of governmental certification on pay is much smaller. Licensing by larger political jurisdictions is associated with higher wage gains relative to only local licensing. We find little association between licensing and the variance of wages, in contrast to unions. Overall, our results show that occupational licensing is an important labor market phenomenon that can be measured in labor force surveys.
urn:nbn:de:101:1-201104113785
Keywords: J08; J44; J58; J80; K23; K31; L38; L5; L51; 330; occupational licensing; labor market institutions; labor market data; wages and labor market institutions; wage inequality and labor market institutions; Qualifikation; Anforderungsprofil; Regulierung; Berufsrecht; Lohnniveau; Lohnstruktur; Schätzung; USA